Acupuncture with plum-blossom needling and cupping therapy for a patient with herpes zoster after chemotherapy for lung cancer (梅花针扣刺联合拔罐治疗1例肺癌患者化疗后并发带状疱疹的护理) - LI Haodong (李浩东); LIU Shuhong (刘书红); ZHAO Yan (赵燕) (中西医结合护理)
This paper investigated the effect of Aupuncture with plum-blossom needling and cupping therapy in treating a case of herpes zoster after chemotherapy for lung cancer, and summarized related nursing measures. Based on the syndrome differentiation, the acupuncture with plum-blossom needling was applied to the area of herpes and the lesion, followed by the cupping therapy. The combined treatment of green nursing techniques can not only relieve the pain and discomfort symptoms caused by herpes zoster, but also improve the quality of life of the patient. (本文总结梅花针扣刺联合拔罐治疗1例肺癌患者化疗后并发带状疱疹的护理体会。基于辨证分型, 采用梅花针扣刺疱疹及病变范围, 再行拔罐, 拔除瘀血, 泄毒排邪, 有效减轻患者疼痛, 缓解不适症状, 有助于提高肿瘤患者的生存质量。)